2012
DOI: 10.1371/journal.pone.0047392
|View full text |Cite
|
Sign up to set email alerts
|

Towards Defining Nutrient Conditions Encountered by the Rice Blast Fungus during Host Infection

Abstract: Fungal diseases cause enormous crop losses, but defining the nutrient conditions encountered by the pathogen remains elusive. Here, we generated a mutant strain of the devastating rice pathogen Magnaporthe oryzae impaired for de novo methionine biosynthesis. The resulting methionine-requiring strain grew strongly on synthetic minimal media supplemented with methionine, aspartate or complex mixtures of partially digested proteins, but could not establish disease in rice leaves. Live-cell-imaging showed the muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
69
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 30 publications
1
69
0
Order By: Relevance
“…The Moarg1, Moarg5,6, and Moarg7 mutants were able to penetrate plant leaf cuticles, but the penetration rate and invasive growth were obviously reduced compared with the wild type, which just like Momet13 and Molys2 mutants of M. oryzae (Yan et al, 2013;Chen et al, 2014). However, studies in str3 (methionine auxotrophy) and Moilv1 (isoleucine auxotrophy) showed that there was no statistical difference in penetration rate between mutants and wild type, but the growth of invasive hyphae was restricted in host cells (Wilson et al, 2012;Du et al, 2014). Taken together, we can conclude that limited appressorium-mediated penetration and restricted invasive hyphae growth in host cells are responsible for the attenuated pathogenicity of auxotrophic mutants.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The Moarg1, Moarg5,6, and Moarg7 mutants were able to penetrate plant leaf cuticles, but the penetration rate and invasive growth were obviously reduced compared with the wild type, which just like Momet13 and Molys2 mutants of M. oryzae (Yan et al, 2013;Chen et al, 2014). However, studies in str3 (methionine auxotrophy) and Moilv1 (isoleucine auxotrophy) showed that there was no statistical difference in penetration rate between mutants and wild type, but the growth of invasive hyphae was restricted in host cells (Wilson et al, 2012;Du et al, 2014). Taken together, we can conclude that limited appressorium-mediated penetration and restricted invasive hyphae growth in host cells are responsible for the attenuated pathogenicity of auxotrophic mutants.…”
Section: Discussionmentioning
confidence: 94%
“…In M. oryzae, two REMI transformants pth3 and met1 have been identified, which exhibit histidine auxotrophy and methionine auxotrophy, respectively (Sweigard et al, 1998;Balhadère et al, 1999). Recently, the functions of several synthetic enzyme genes involved in methionine (MET12, MET13 and STR3), leucineisoleucine-valine (ILV1, ILV2 and ILV6), lysine (LYS2), and purine (ADE1) biosynthesis were investigated in M. oryzae (Yan et al, 2013;Wilson et al, 2012;Du et al, 2013Du et al, , 2014Chen et al, 2014;Fernandez et al, 2013). A link between auxotrophy and the loss of, or a reduction in pathogenicity was found in most of these cases.…”
Section: Introductionmentioning
confidence: 99%
“…Nutrient metabolism plays important roles in the growth and differentiation of M. oryzae , which blocks amino acid biosynthesis and causes defects in growth, asexuality, and virulence (Wilson et al, 2012; Du et al, 2013; Yan et al, 2013). In this study, we characterized the CPS large subunit, MoCpa2, in M. oryzae and found that the Δ Mocpa2 mutant could not grow on MM plates.…”
Section: Discussionmentioning
confidence: 99%
“…The regulatory systems include nitrogen metabolite repression (NMR) and carbon catabolite repression (CCR) to ensure the use of preferred sources of nitrogen (ammonium and L-glutamine) and carbon (glucose), respectively (Wilson et al, 2007, 2012; Wilson and Talbot, 2009; Fernandez et al, 2012). Both NMR and CCR are controlled by a Tor signaling pathway that regulates growth in response to nutrient availability (Franceschetti et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation